Evaluation of the Catchment Parameter (CAPA) and Midgley and Pitman (MIPI) empirical design flood estimation methods - Smal, Ruan (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.